Improving the management system through the formation of modern managers and employees in enterprises and organizations - Rasulova Gulnoza Fayzullaevna (International Journal on Economics, Finance and Sustainable Development, 2021)
This article forms the conceptual framework of modern management and personnel management structure, structural information and perspective directions of development of enterprises by managers and employees in the activities of industries and enterprises in the context of modernization of the economy. Data on the role and requirements of managers and employees in the effective operation of enterprises and organizations today, the improvement of the management system, the formation of management culture and management knowledge were analyzed and recommendations for improving management were developed